Pengajaran Musik Bambu (Angklung) untuk Meningkatkan Pembelajaran Seni Musik - Hikmawati Usman; Nasaruddin Nasaruddin; Sayidiman Sayidiman (DEDIKASI, 2019)
This study was conducted based on several factors such as the lack of students’ knowledge in playingtraditional music instruments and the lack of training to develop their talents. The result of this study showed thatthe main issue in training are 1) the students have not understand the importance of bamboo music instruments(angklung), 2) not many of the students play this bamboo instruments (angklung), 3) the students still lack ofpracticing play bamboo instruments (angklung).